2009
DOI: 10.1111/j.1751-1097.2008.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Intensity Helium–Neon (HeNe) Laser Irradiation on Experimental Paracoccidioidomycotic Wound Healing Dynamics

Abstract: The effect of HeNe laser on the extracellular matrix deposition, chemokine expression and angiogenesis in experimental paracoccidioidomycotic lesions was investigated. At days 7, 8 and 9 postinfection the wound of each animal was treated with a 632.8 nm HeNe laser at a dose of 3 J cm . At day 10 postinfection, the wounds were examined by using histologic and immunohistochemical methods. Results revealed that lasertreated lesions were lesser extensive than untreated ones, and composed mainly by macrophages and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
5
1
3
Order By: Relevance
“…This demonstrated that laser therapy increases the phagocytic capacity of macrophages, facilitating cleaning of the wound. 22 Although the literature questions the influence of the environment around the bacteria and the application of laser in such circumstances, our study did not observe statistically significant differences when comparing the use of lasers in intact skin and wounds, resulting in a significant reduction in both cases. 6,13,21,22 …”
Section: Discussioncontrasting
confidence: 59%
“…This demonstrated that laser therapy increases the phagocytic capacity of macrophages, facilitating cleaning of the wound. 22 Although the literature questions the influence of the environment around the bacteria and the application of laser in such circumstances, our study did not observe statistically significant differences when comparing the use of lasers in intact skin and wounds, resulting in a significant reduction in both cases. 6,13,21,22 …”
Section: Discussioncontrasting
confidence: 59%
“…23 It is described as ranging from 4 to 10 J/cm 2 for soft tissues. [35][36][37][38][39] In light of this information, the laser doses selected were 10 and 20 J/cm 2 in this investigation. Although some researchers reported that there is no relationship between the cortical bone thickness and the stability of the mini screw, [40][41][42] others reported an opposing argument.…”
Section: Discussionmentioning
confidence: 99%
“…Após a determinação do tempo, foi escolhida uma mácula e aplicado o UVB perpendicular com 10 cm de afastamento da pele O L.A.S.E.R. que pode ser utilizado para tratamento dessa patologia é o HeNe, que é de baixa energia e emite radiação em espectro de luz visível (10). Estudos demonstram que, além de modulação dos queratinócitos, ibroblastos e melanoblastos, o tratamento induz a síntese do fator de melanócitos relacionados com o crescimento, estimulando a proliferação de melanócitos.…”
Section: Procedimentos De Intervençãounclassified
“…A etiologia e patogenia exata da doença são desconhecidas. Existem teorias como as hipóteses neural, imune e autodestrutiva (6)(7)(8)(9)(10). A caracterização do vitiligo sugere que fatores predisponentes (genéticos) e precipitantes (ambientais) tornam uma pessoa mais suscetível à doença.…”
Section: Introductionunclassified